Innovation Of Islamic Relegious Systems In Improving Student Character Education In Mts Darussalam, Demak - Kamilia, Farah; Zafi, Ashif Az (Tawazun: Jurnal Pendidikan Islam, 2021)
Technology and science have developed rapidly by following the times that exist so as to provide changes to the world, especially the world of education. With this change, an innovation is needed in order to improve character education, especially in the Islamic Religious Education system at MTs Darussalam Jetak Demak. This research was conducted with the aim of knowing that basically in educational institutions it certainly requires an educational innovation so that the desired goals can be achieved by solving problems that exist in education. In addition, if there is innovation in the education system, it will be able to produce a generation who is intelligent in reason and has a good spiritual attitude. That way, to realize good and qualified student character education, it must provide an innovation in education, especially by optimizing the learning material of Islamic Religious Education at MTs Darussalam Jetak Demak. The method used in this research is a type of qualitative research which is carried out using ethnographic methods, namely research which is carried out by solving a problem such as conducting interviews and extracting information so that it is collected into effective and efficient data. Therefore, the results of this study are the innovation of the Islamic Religious Education system greatly influences the development of students at MTs Darussalam Jetak Demak, especially on improving the quality of student character education, so as to realize a learning system in accordance with the plan that has been designed through various techniques and methods. learning provided by educators. Abstrak Teknologi dan ilmu pengetahuan berkembang pesat mengikuti perkembangan zaman yang ada sehingga memberikan perubahan pada dunia khususnya dunia pendidikan. Dengan adanya perubahan tersebut maka diperlukan suatu inovasi dalam rangka meningkatkan pendidikan karakter khususnya pada sistem Pendidikan Agama Islam di MTs Darussalam Jetak Demak. Penelitian ini dilakukan dengan tujuan untuk mengetahui bahwa pada dasarnya dalam lembaga pendidikan tentunya membutuhkan suatu inovasi pendidikan agar tujuan yang diinginkan dapat tercapai dengan pemecahan masalah yang ada dalam pendidikan. Selain itu, jika ada inovasi dalam sistem pendidikan akan mampu menghasilkan generasi yang cerdas akal dan memiliki sikap spiritual yang baik. Dengan begitu, untuk mewujudkan pendidikan karakter siswa yang baik dan berkualitas maka harus memberikan suatu inovasi dalam pendidikan khususnya dengan mengoptimalkan materi pembelajaran Pendidikan Agama Islam di MTs Darussalam Jetak Demak. Metode yang digunakan dalam penelitian ini adalah jenis penelitian kualitatif yang dilakukan dengan menggunakan metode etnografi, yaitu penelitian yang dilakukan dengan cara memecahkan suatu masalah seperti melakukan wawancara dan penggalian informasi sehingga terkumpul menjadi data yang efektif dan efisien. Oleh karena itu, hasil dari penelitian ini adalah inovasi sistem Pendidikan Agama Islam sangat berpengaruh terhadap perkembangan siswa di MTs Darussalam Jetak Demak khususnya terhadap peningkatan kualitas pendidikan karakter siswa, sehingga dapat mewujudkan sistem pembelajaran yang sesuai dengan rencana. yang telah dirancang melalui berbagai teknik dan metode. pembelajaran yang diberikan oleh pendidik.